Molecular Characteristics of Staphylococcus aureus From Food Samples and Food Poisoning Outbreaks in Shijiazhuang, China - Lv, Guoping; Jiang, Ruiping; Zhang, Han; Wang, Lei; Li, Lijie; Gao, Weili; Zhang, Hong; Pei, Yantao; Wei, Xiuping; Dong, Hongyan; Qin, Liyun (Frontiers in Microbiology, 2021)
As an opportunistic pathogen worldwide, Staphylococcus aureus can cause food poisoning and human infections. This study investigated the sequence typing, the penicillin (blaZ) and methicillin (mec) resistance profiles of S. aureus from food samples and food poisoning outbreaks in Shijiazhuang City and the staphylococcal enterotoxin types of the S. aureus isolates from food poisoning. A total of 138 foodborne S. aureus isolates were distributed into 8 clonal complexes (CCs) and 12 singletons. CC1, CC5, CC8, CC15, CC97, CC59, CC398, CC88 and CC7 were the predominant CCs of foodborne S. aureus isolates. And CC59, CC15 and CC5 were the most prevalent CCs in food poisoning outbreaks. SEE was the most commonly detected staphylococcal enterotoxin in food poisoning isolates. 133 S. aureus isolates harbored the penicillin resistant gene blaZ, and 9 isolates carried mec gene. The present study further explained the relationship between S. aureus and foods and food poisoning and indicated the potential risk of S.aureus infection.